The Influence of the Problem-Based Learning (PBL) Model on Students’ Critical Thinking Skills in Indonesian History Learning for Grade X Social Science Class at MAN 2 Tangerang - Dewi Yuliani; Ana Nurhasanah; Yuni Maryuni (UNIVERSITAS MUHAMMADIYAH METRO, 2026)
This study aims to determine the influence of the problem-based learning (PBL) model on students’ critical thinking skills in Indonesian history learning for Grade X Social Science class at MAN 2 Tangerang. The research was conducted from March 8, 2023, to April 12, 2023. The method employed was a quasi-experiment, using a non-probability sampling technique, with 39 students in both the experimental and control classes. The instrument used in this study was an essay test consisting of 9 items. The hypothesis was tested using the t-test with the pooled variance formula, resulting in a calculated t-value of 2.479, which is greater than the critical t-table value of 1.991 at Î± = 0.05. Therefore, Ha was accepted and Ho was rejected. This finding indicates that the problem-based learning model significantly influences students’ critical thinking skills in Indonesian history learning.